A Systematic Analysis and Experimental Verification of Joint Pricing and Inventory Strategies in Competitive Newsvendor Environments - Mengmeng Shi; Yue Liu; Shaohui Wu (Systems)
This study examined joint pricing and inventory decisions in a competitive newsvendor environment using a combination of theoretical modeling and experimental methods. We developed a newsvendor model with price competition and inventory decisions. Participants in a laboratory experiment made simultaneous pricing and inventory decisions over 50 rounds, with their opponents’ identities unknown. We theoretically proved the existence of a mixed Nash equilibrium, i.e., different equilibrium prices corresponded to different optimal inventory quantities. The experimental results show that about <semantics>50%</semantics> of the joint pricing and inventory decisions were consistent with the predictions of the equilibrium model. However, systematic deviations from the equilibrium predictions were also observed at the aggregate level. We developed a novel context-dependent quantal response equilibrium model (QRE) for the bivariate newsvendor game setting. The context-dependent quantal response equilibrium model fit the observed decision biases remarkably well, and it was significantly better than the basic QRE model. This research provides insights into decision biases in complex systems and practical guidance for project planning and management.